The impact of the differentiated education strategy on the level of achievement in the subject of vocational education among Tenth grade students in Jordan - Alhabahbeh, Basmah Abdallah Odeh (Journal of Educational and Psychological Sciences, 2020)
The present study aimed at identifying the effect of differentiated education strategy on the level of achievement in the subject of vocational education among the Tenth grade students in Jordan. The study adopted the semi-experimental curriculum. The tool consisted of (Achievement Test in Vocational Education), prepared by the researcher, was applied to a random sample of two divisions of the ninth grade students at the Hashemite Secondary School for Girls, affiliated to the Directorate of Education in Aqaba during the academic year 2018/2019, to Division (B) As an experimental group, it consisted of (20) female students, and Division (A) as a control group, and consisted of (20) female students. The results of the ANCOVA analysis showed that there were statistically significant differences between the students’ average scores on the achievement test due to the variable of teaching method, where the control group obtained an overall average (13.03) in exchange for the experimental group obtained an overall average (17.95). In the light of the results of the study, the researcher recommended the training of teachers on the differentiated teaching strategy in teaching vocational education for its effectiveness in teaching and conducting studies dealing with the introduction of other teaching methods.